Swiping Toward Self-Efficacy: What Students Say About Learning English Through TikTok - Hidayat, Wahyu; Lolita, Yuri (JADEs Journal of Academia in English Education, 2025)
This study aims to investigate how high school students view TikTok as a tool for enhancing their self-efficacy in learning English. Over the course of three weeks, 32 grade XI students from a Gresik public school participated in the study, which used a qualitative case study methodology. Semi-structured interviews, classroom observations, and student video analysis were used to gather data. The findings demonstrated that TikTok usage greatly improved students' motivation to use English both within and outside of the classroom, as well as their engagement, speaking confidence, and comprehension of the subject matter through multimodal aspects (text, visual, and audio). Peer support and a collaborative classroom environment effectively maintained students' positive evaluations of TikTok as an effective learning medium, despite obstacles including early shyness and the digital gap. According to this study, TikTok can be a meaningful, entertaining, and contextualized learning tool for the current digital generation.